(untitled) (Research, Society and Development, 2019)
The article talks about gestational cancer. This type of neoplasm occurs only in pregnant women, or until one year after delivery, where it includes the lactation phase. The index is still relatively "small," but, as has been observed in the studies, these numbers are growing more and more. For women today are extending their gestation in search of their financial freedom. This is a bibliographical review, performed through the search of electronic journals, manuals, ordinances and government websites, presenting data on gestational cancer in Brazil. It is concluded that this neoplasm is a serious disease. Thus, it is important that health professionals, especially nursing, have the knowledge on this subject, for its constant updating. This article aims to explain the importance of knowledge about gestational cancer and to show that over the course of the days, gestational cancer is increasingly common among pregnant women.